Analysis of Microplastics in Industrial Processes—Systematic Analysis of Digestion Efficiency of Samples from Forestry, Wastewater Treatment Plants and Biogas Industries - Blaž Hrovat; Emilia Uurasjärvi; Arto Koistinen (Microplastics)
Microplastics (MPs) are persistent, globally relevant pollutants that have thus far been rigorously studied in natural waters but have not been as extensively studied in industrial wastewaters. Samples were collected from the forestry industry, wastewater treatment plants and the biogas industry. An enzymatic treatment protocol for MPs’ detection was applied to an assortment of industrial samples ranging from wastewaters, effluents and condensates to sludges and digestates. The effects of selected enzymes were studied systematically to develop a basis for digestion protocols on industrial samples. Further, different methods of detection (micro FTIR and Raman) were compared to each other, and the samples were visually examined using SEM. The developed protocols in this study were then compared with blank samples, contamination controls and samples spiked with artificial microplastics. This research aimed to fill some of the gap in the knowledge regarding the analysis methods and especially in the type of samples screened for microplastics thus far and presents a systematic approach to MPs’ detection in industrial wastewaters. It highlights the issues with the used analytical methods (such as misidentification) and validates the analysis results with milled, random shape and wide-size-range reference MPs that represent real samples better than standardized, ideal round beads. This study provides the first-ever suggestion for an enzymatic digestion protocol for industrial sample analysis.